Hazard Identification and Risk Management for Occupational Safety and Health at PT. PLN (Persero) Transmisi dan Gardu Induk Meulaboh - Pamungkas, Iing; Akmal, Abdiel Khaleil; Irawan, Heri Tri; Azhar (Jurnal Inotera, 2025)
This research aims to identify the sources of Occupational Safety and Health (OSH) hazards at PT. PLN (Persero) Transmisi dan Gardu Induk Meulaboh and to control the risks of OSH hazards at PT. PLN (Persero) Transmisi dan Gardu Induk Meulaboh. Focusing on power transmission, PT. PLN (Persero) Transmisi dan Gardu Induk Meulaboh is always committed to improving the quality and continuity of service to customers. However, considering the high inherent risks in electrical activities, the company realizes the importance of prioritizing safety and health at work (OSH) as an integral part of its operations. Given the high risks associated with electrical activities, this company needs to proactively identify and manage potential hazards that could threaten the safety of workers. Hazard identification, risk assessment, and determining control (HIRADC) are used to identify potential hazards, assess risks, and determine appropriate control measures for those hazards. HIRADC consists of three main stages, namely hazard identification, risk assessment, and hazard control. The results of the hazard and risk identification show that work activities at PT. PLN (Persero) Transmisi dan Gardu Induk Meulaboh contain a number of significant potential hazards including the risk of electric shock, exposure to hazardous chemicals, high noise levels, the potential to be struck by equipment, the risk of leaks, and the danger of fire. The consequences of exposure to these hazards can vary, ranging from minor injuries to fatal injuries. Some control measures that can be taken include the use of appropriate Personal Protective Equipment (PPE), the installation of hazard warning signs, and the implementation of safe work procedures.